Large Purcell enhancement with efficient one-dimensional collection via coupled nanowire–nanorod system. (21st December 2017) - Duan, Xueke; Ren, Juanjuan; Zhang, Fan; Hao, He; Lu, Guowei; Gong, Qihuang; Gu, Ying
Abstract: Combining the advantages of both gap surface plasmons (GSPs) and evanescent waves, we demonstrate simultaneously large Purcell enhancement and efficient one-dimensional collection of photons at subwavelength scale in the coupled nanowire–nanorod system. The spontaneous emission (SE) can be enhanced thousands of times based on the excitation of GSPs with strongly localized electromagnetic field. Emitted photons are directly collected by subwavelength-confined evanescent modes and guided along the nanowire. By optimizing geometry and material parameters, 14 208 times of Purcell enhancement with collection efficiency up to 39.3% can be achieved in the Ag nanowire–Ag nanorod system where the emitted photons can spread more than 25 μ m, or SE is enhanced by 3142 times and up to 53% of emitted photons propagate with low loss in the dielectric nanowire–Ag nanorod system. This proposal that incorporates large Purcell enhancement, efficient nanoscale collection and one-dimensional propagation of photons, promises to have an important impact on bright single photon sources, plasmon-based nanolasers and on-chip nanodevices.